EFEKTIVITAS PENGGUNAAN APLIKASI ZOOM SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF PADA MAHASISWA ILMU KOMUNIKASI UMI MAKASSAR - NurSa’adah Awlia Abdul Hamid; Amaluddin Amaluddin; Abd Majid (UNIVERSITAS MUSLIM INDONESIA, 2020)
Due to the spread of COVID-19 in Indonesia, all students in Indonesia are required to study online at home. Faculty of Letters, Communication Studies Study Program UMI Makassar is one of the campuses that implements online learning using the Zoom application. Zoom Cloud meeting is one of the online learning media that is often used at the Faculty of Letters, Communication Studies Study Program, UMI Makassar. The effectiveness of online learning really needs to be considered so that students understand when learning takes place. The purpose of this study is to find out and understand how effective online learning is using the Zoom application as an interactive learning medium at UMI Makassar Communication Science. This research uses descriptive qualitative research. The primary and secondary data sources where primary data is a source of data obtained directly using the method of observation and interviews, polls from individuals or groups, while secondary is a source of data obtained through media intermediaries or indirectly in the form of books. the method used is the method of observation, interviews and documentation. The results showed that the effectiveness of using the Zoom application as an interactive learning medium for Communication Science students at UMI Makassar, the presence of the covid-19 virus could be said to be ineffective in terms of interactive learning, but in terms of using the Zoom video conference application, of course, it really supports the distance learning process due to restrictions on activities that are carried out. issued by the government during a pandemic. The obstacles during the learning process using the Zoom application are minimal internet quota and an unstable network.